AB0558 What is the Prevalence of NON Criteria Antiphospholipid Antibodies in Patients with Antiphospholipid Syndrome?. (10th June 2014) - Rodríguez-García, V.; Ioannou, Y.; Fernández-Nebro, A.; Isenberg, D.A.; Giles, I.
Abstract : Background: Increasing interest has focussed upon assays which are not currently included in the Antiphospholipid syndrome (APS) classification criteria to detect antibodies directed against other phospholipids (PL), PL binding proteins and/or coagulation factors. Objectives: We carried out a systematic review to establish the prevalence of each non-criteria assay in APS and control populations. Methods: We searched PubMed and EMBASE using the keywords APS, antiphospholipid antibodies (aPL), non criteria, new assays, aCL, LA, anti-Domain I (aDI), anti-β2GPI, antiphosphatidylserine (aPS), antiphosphatidylethanolamine (aPE), antiphosphatidic acid (aPA), antiprothrombin (aPT), antiphosphatidylserine-prothtombin (aPS-PT), anti-cardiolipin/vimentin (CL/Vm) and Annexin A5 resistance (AnxA5R). Each publication was systematically examined. Results: We selected 14 (4 retrospective, 2 case-control and 8 cross-sectional) studies from which we were able to extract original data on prevalence of non-criteria aPL in 1307 patients with APS and 1612 disease controls and 625 healthy controls. Conclusions: The highest prevalence of non-criteria aPL in the largest number of patients with APS was found in studies of IgA anti β2GPI (56.33% in 229 APS patients), AnxA5R (53.37% in 163 APS patients) and IgG aDI (44% in 548 APS patients). All non-criteria aPL studied were found to be significantly raised in APS compared with controls. Most studies however, were confounded by: small sample size, retrospective collection; and different determination of positivity. Therefore, further prospective studies are urgently required to confirm these findings. References: Miyakis S, Lockshin MD, Atsumi T, Branch DW, Brey RL, Cervera R, et al. International consensus statement on an update of the classification criteria for definite antiphospholipid syndrome (APS). J Thromb Haemost JTH. 2006 Feb;4(2):295–306. Garcia D, Akl EA, Carr R, Kearon C. Antiphospholipid antibodies and the risk of recurrence after a first episode of venous thromboembolism: a systematic review. Blood. 2013 Aug 1;122(5):817–24. Tincani A, Andreoli L, Casu C, Cattaneo R, Meroni P. Antiphospholipid antibody profile: implications for the evaluation and management of patients. Lupus. 2010 Apr;19(4):432–5. Wilson WA, Gharavi AE, Koike T, Lockshin MD, Branch DW, Piette JC, et al. International consensus statement on preliminary classification criteria for definite antiphospholipid syndrome: report of an international workshop. Arthritis Rheum. 1999 Jul;42(7):1309–11. Lee RM, Branch DW, Silver RM. Immunoglobulin A anti-beta2-glycoprotein antibodies in women who experience unexplained recurrent spontaneous abortion and unexplained fetal death. Am J Obstet Gynecol. 2001 Sep;185(3):748–53. Lakos G, Kiss E, Regëczy N, Tarján P, Soltész P, Zeher M, et al. Isotype distribution and clinical relevance of anti-beta2-glycoprotein I (beta2-GPI) antibodies: importance of IgA isotype. Clin Exp Immunol. 1999 Sep;117(3):574–9. De Laat B, Pengo V, Pabinger I, Musial J, Voskuyl AE, Bultink IEM, et al. The association between circulating antibodies against domain I of beta2-glycoprotein I and thrombosis: an international multicenter study. J Thromb Haemost JTH. 2009 Nov;7(11):1767–73. Disclosure of Interest: V. Rodríguez-García Grant/research support: FER grant from The Spanish Society of Rheumatology, Y. Ioannou: None declared, A. Fernández-Nebro: None declared, D. A. Isenberg: None declared, I. Giles: None declared DOI: 10.1136/annrheumdis-2014-eular.2749